Ground Motion and Site Characteristics Evaluation Using Hilbert-Huang Transform Method Based on Light-Moderate Earthquakes - Jinchang Chen; Lanmin Wang; Ailan Che; Hanxu Zhou (Shock and Vibration)
Compared with strong earthquakes (Ms ≥ 6.0), light-moderate earthquakes (Ms 4–5.9) occurred more frequently and distributed more widely, and rich ground motions have been collected around world. It provides a solid data base for the investigation on the ground motion and regional site characteristics which are closely related to seismic geological disaster. We chose two light-moderate earthquakes in China as study cases. Based on Hilbert-Huang transform, we analyzed the ground motion characteristics in time-frequency domain. Using a stable coda wave and marginal spectrum of it based on horizontal to vertical Fourier spectral ratio (HVSR) method, the site characteristics are clarified. Result shows that the amplitude (instantaneous frequency energy) of Hilbert-Huang spectrum is mainly concentrated within 20 Hz at the stations that are close to epicenter. The energy will change from concentration to divergence in time and frequency and decrease with the increase of epicenter distance under soil site condition. Two earthquakes present a low prominent frequency characteristic (1.075–2.45 Hz). Hilbert energy at soil layer is about 3 times greater than it at rock site when the epicenter distance is close and soil layer can also amplify the instantaneous energy. The predominant frequency of site at each station is within 3.6–6.2 Hz. The predominant frequencies of the earthquakes are lower than the predominant frequencies of the sites and would not produce resonance effects. The result can provide meaningful references for later study works about the characteristics and application of light-moderate earthquakes.